Behavior of an almost semicontinuous Poisson process on a Markov chain upon attainment of a level - Karnaukh, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider almost semicontinuous processes defined on a Markov chain and obtain representations for the generatrices of the absolute maximum upon attainment of a positive level and the recovery time. Modified processes with two-step intensities of negative jumps are investigated.